Optimizing the Effectiveness of the Ketodiet in Parkinson`S Disease (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The goal of this review was to assess the effectiveness of ketogenic diets on the therapy of neurodegenerative diseases. The ketogenic diet is a low-carbohydrate and fat-rich diet. Its implementation has a fasting-like effect, which brings the body into a state of ketosis. The ketogenic diet has, for almost 100 years, been used in the therapy of drug-resistant epilepsy, but current studies indicate possible neuroprotective effects. Thus far, only a few studies have evaluated the role of the ketogenic diet in the prevention of Parkinson's disease (PD) and Alzheimer's disease (AD). Single studies with human participants have demonstrated a reduction of disease symptoms after application. The application of the ketogenic diet to elderly people, however, raises certain concerns. Persons with neurodegenerative diseases are at risk of malnutrition, while food intake reduction is associated with disease symptoms. In turn, the ketogenic diet leads to a reduced appetite; it is not attractive from an organoleptic point of view, and may be accompanied by side effects of the gastrointestinal system. Parkinson disease is the most common form of parkinsonism, a group of neurological disorders with Parkinson disease-like movement problems such as rigidity, slowness, and tremor. More than 6 million individuals worldwide have Parkinson disease. Parkinson's disease (PD) is the second most prevalent neurodegenerative disease, and oxidative stress and mitochondrial dysfunction play a major role in the pathogenesis of PD. Since conventional therapeutics are not sufficient for the treatment of PD, the development of new agents with anti-oxidant potential is crucial